2021
DOI: 10.4081/jlimnol.2021.2052
|View full text |Cite
|
Sign up to set email alerts
|

Pioneer annual vegetation of gravel-bed rivers: first insights on environmental drivers from three Apennine streams

Abstract: A huge knowledge gap exists on riverine pioneer herbaceous vegetation. Despite its relevance in regulating the C metabolism at the catchment scale, and the triggering role in shrubs and trees establishment along riverbanks, little data is available on its environmental determinants. Indeed, most existing knowledge in this field refers to woody species or aquatic macrophytes neglecting the ecosystem relevance of ephemeral herbaceous vegetation. Focusing on three gravel bed rivers located in northern Italy (Baga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Comparable results have been recently recorded by Bolpagni and Dalla Vecchia (2021) for a set of intermittent streams in the same hydrological basin of the current rivers studied (Po River plain, Northern Italy), although under completely different geomorphological and hydrological conditions (e.g., intermittent vs. permanent regimes). The authors indicated the progressive replacement of the typical ‘pioneer riverine plants’ by ruderal taxa not strictly riparian, following the categories defined by Tabacchi et al (1996): a dynamic vegetation process that may be ascribed to the progressive increase in hydrological disconnection of seasonally exposed fluvial forms.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Comparable results have been recently recorded by Bolpagni and Dalla Vecchia (2021) for a set of intermittent streams in the same hydrological basin of the current rivers studied (Po River plain, Northern Italy), although under completely different geomorphological and hydrological conditions (e.g., intermittent vs. permanent regimes). The authors indicated the progressive replacement of the typical ‘pioneer riverine plants’ by ruderal taxa not strictly riparian, following the categories defined by Tabacchi et al (1996): a dynamic vegetation process that may be ascribed to the progressive increase in hydrological disconnection of seasonally exposed fluvial forms.…”
Section: Discussionsupporting
confidence: 86%
“…This wide hydrological variability alters the ‘natural’ dynamism of rivers and, in turn, the ‘natural’ structure of riverbeds lowering the complexity of riverine mesohabitats, including the spatial representativeness and the structure of islands, sandbars and scree deposits. All this can strongly affect riverbed vegetation dynamics and functioning, especially of pioneer plant communities able to establish on seasonally exposed sediments (Bolpagni & Dalla Vecchia, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation